SISTEM INFORMASI PENGOLAHAN DATA NILAI SISWA DENGAN MENGGUNAKAN DATABASE MYSQL - Ahmad, Istna Rahmania (Jurnal Sistem Komputer, 2021)
This research was conducted aiming to generate the value of the data processing information system web-based students who can cultivate the student's grades and recap the value students who are easily accessible and valid. In this study the methods used namely Research and Development that starts from the preliminary studies, design and creation of information systems, systems validation, test users, user test results, analysis of the results of the user, and then pull conclusion. As for the testing system using test black box and test user response. The average results obtained from 84.26% of respondents answer. The results of the calculation to test the response of users obtained eligibility percentages of 84.26%. This research it can be concluded from the information system processing the data value of the excellent students help teachers in the menginputkan value and is worthy of being used as student information system processing the data value of the students.